2,1,3-Benzoselenadiazole as Mono- and Bidentate N-Donor for Heteroleptic Cu(I) Complexes: Synthesis, Characterization and Photophysical Properties - Valentina Ferraro; Fabian Hoffmann; Olaf Fuhr; Burkhard Luy; Stefan Bräse (Inorganics, 2024)
Mono- and binuclear Cu(I) complexes were isolated employing 2,1,3-benzoselenadiazole (BSeD) as the N-donor ligand, and triphenylphosphine or bis[(2-diphenylphosphino)phenyl] ether (DPEphos) as P-donors. Then, 77Se NMR was measured for the free ligand and the corresponding Cu(I) derivatives, and the related signal was downshifted by 12.86 ppm in the case of [Cu(BSeD)(PPh3)2(ClO4)], and around 15 ppm for the binuclear species. The structure of [Cu(BSeD)(PPh3)2(ClO4)] and [Cu2(μ2-BSeD)(DPEphos)2(ClO4)2] was confirmed by single-crystal X-ray diffraction. The geometry of the Cu(I) complexes was optimized through DFT calculations, and the nature of the Cu···O interaction was investigated through AIM analysis. The three Cu(I) complexes were characterized by intense absorption under 400 nm and, after being excited with blue irradiation, [Cu(BSeD)(PPh3)2(ClO4)] and [Cu2(μ2-BSeD)(PPh3)4(ClO4)2] exhibited weak red emissions centered at 700 nm. The lifetimes comprised between 121 and 159 μs support the involvement of triplet excited states in the emission process. The photoluminescent properties of [Cu(BSeD)(PPh3)2(ClO4)] were supported by TDDFT computations, and the emission was predicted at 710 nm and ascribed to a metal-to-ligand charge transfer (3MLCT) process, in agreement with the experimental data.